Factors That Influence The Earning Response Coefficient In Property And Real Estate Sector Companies In Indonesia - Widarti Widarti; Dwi Yanti; Ferdiansyah Sugiarto (UNIVED Press, 2025)
This study aims to determine the effect of Profitability, Company Size, Leverage, and Growth Opportunities on Earning Response Coefficient. This type of research data is quantitative data, the technique used in sampling for this study is using purposive sampling technique. The purposive sampling technique is a sampling technique to select samples based on several criteria so that later the samples used are more representative. The data obtained is then processed and tested so that it can be concluded how the Effect of Profitability, Company Size, Leverage, and Growth Opportunities on Earning Response Coefficient. The results of this study. Profitability, Growth Opportunities, Company Size and Leverage variables have an overall and statistically significant effect on ERC. The F statistic value of 1.425 with a significance value (Sig.) of 0.032 indicates that the regression model used has a significant effect simultaneously on the dependent variable, namely the Earning Response Coefficient (Y).